2017
DOI: 10.1111/1477-8947.12124
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the impacts of the national housing programme on the accessibility of the low‐income population in Rio de Janeiro

Abstract: The Brazilian shift from a primarily rural to a more urban society has created major challenges that public policies must address. One of the most relevant challenges is deep social exclusion in urban areas, especially in terms of adequate housing and access to urban opportunities (e.g., jobs, housing, and services). In this context, land use and transport planning play a critical role in the sustainable development agenda. The work presented here analyses the accessibility of low-income dwellings licenced und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Brazilian cities are no exception. Through a study in Rio de Janeiro, Barandier, Bodmer, and Lentino (2017) found that urban sprawl results in transport accessibility issues and concernedly high commute times, especially because of the country's significant disparity between the rich and the poor, allowing the wealthy to depend heavily on private automobiles, while the low-income population faces social exclusion and disadvantage. Haddad and Barufi (2017) present similar findings, showing that low-income residents in the São Paulo Metropolitan Region are more likely to rely on public transportation, facing longer commute times and lower job accessibility.…”
Section: Spatial Mismatch Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Brazilian cities are no exception. Through a study in Rio de Janeiro, Barandier, Bodmer, and Lentino (2017) found that urban sprawl results in transport accessibility issues and concernedly high commute times, especially because of the country's significant disparity between the rich and the poor, allowing the wealthy to depend heavily on private automobiles, while the low-income population faces social exclusion and disadvantage. Haddad and Barufi (2017) present similar findings, showing that low-income residents in the São Paulo Metropolitan Region are more likely to rely on public transportation, facing longer commute times and lower job accessibility.…”
Section: Spatial Mismatch Hypothesismentioning
confidence: 99%
“…Bringing the two together allows me to bridge part of Chetty et al (2014) approach to the Global South. Even though several quantitative studies have focused on commuting time in the context of Brazilian cities (Tigre, Sampaio, & Menezes, 2017;Miranda & Domingues, 2010;Silveira Neto, Duarte, & Páez, 2015;Motte, Aguilera, Bonin, & Nassi, 2016;Barandier et al, 2017;Haddad and Barufi, 2017), there is no study that directly addresses the connections between residential segregation and time spent commuting to work.…”
Section: Spatial Mismatch Hypothesismentioning
confidence: 99%
“…Under these conditions, the economic, social and territorial consequences have been subject to discussion within urban studies. While it has been acknowledged that market-driven schemes increased considerably the number of delivered housing units thus tackling successfully housing deficits, they have been criticised to exacerbate social segregation by displacing the poor to ever more peripheral locations (Barandier et al, 2017;Dohnke et al, 2015;Gaffney, 2010;Rolnik et al, 2015;Tapia, 2012). In the same way as during previous times of state-driven promotions, contemporary lowincome housing schemes fundamentally focus on standardised housing types that deny liveable urban habitat and fall short of considering individual circumstances of the .…”
Section: E a Characterisation Of Low-income Housing In Latin Americanmentioning
confidence: 99%
“…Interviews were recorded and transcribed. 2 For instance, the expansion of peripheral low-income housing has been similarly intensive in countries such as Chile and Brazil(Barandier et al, 2017;Imilan, 2016).…”
mentioning
confidence: 99%
“…Although a certain amount of the literature pertains to accessibility evaluation, most of these studies focus on a single type of facility, particularly the spatial accessibility of public transport [23,29], green spaces [30,31], educational services [32,33], and healthcare services [34,35]. Few empirical studies have evaluated the integrated spatial accessibility of multiple types of public facilities (except [24,27]).…”
Section: Introductionmentioning
confidence: 99%